Impaired serological response to COVID‐19 vaccination following anticancer therapy: A systematic review and meta‐analysis. Issue 10 (6th July 2022) - Tang, Kefu; Wei, Zhiying; Wu, Xi
Abstract: Owing to the high coronavirus disease 2019 (COVID‐19)‐related morbidity and fatality rate among patients with cancer, the introduction of COVID‐19 vaccines is of profound significance in this fragile population. Accumulating data suggested that oncologic patients, especially those with anticancer therapy have an impaired immune response to COVID‐19 vaccination. However, the exact effect of anticancer treatments on postvaccination response has not been elucidated yet. We, therefore, conducted a meta‐analysis to evaluate the impact of treatments on response to COVID‐19 vaccination in patients with cancer. A total of 39 studies were finally included comprising 11 075 oncologic patients. Overall, we found the humoral response was significantly decreased in patients undergoing anticancer treatments (odds ratio [OR] = 2.55, 95% confidence interval [CI]: 2.04–3.18) compared with those without active treatment. The seroconversion rates were significantly lower in patients with chemotherapy (OR = 3.04, 95% CI: 2.28–4.05), targeted therapy (OR = 4.72, 95% CI: 3.18–7.01) and steroid usage (OR = 2.19, 95% CI: 1.57–3.07), while there was no significant association between immunotherapy or hormonal therapy and seroconversion after vaccination. Subgroup analyses showed therapies with anti‐CD20 antibody (OR = 11.28, 95% CI: 6.40–19.90), B‐cell lymphoma 2 inhibitor (OR = 5.76, 95% CI: 3.64–9.10), and Bruton tyrosine kinase inhibitor (OR = 6.86, 95% CI: 4.23–11.15) were significantly correlated with the risk of negative humoral response to vaccination. In conclusion, our results demonstrated that specific oncologic therapies may significantly affect serological response to COVID‐19 vaccines in patients with cancer. Thus, an adapted vaccination strategy taking the influence of active treatment into account is in need, and further research on the effect of the third dose of vaccine and the role of postvaccination cellular response in oncologic patients is also needed.